Hajat lembur: a disaster literacy on ritual communication on the Lembang fault - Evi Rosfiantika; Rinda Aunillah; Budi Gustaman (Jurnal Studi Komunikasi, 2024)
The Hajat Lembur is a yearly ritual by Batu Lonceng Villagers, in West Bandung-Indonesia, following the 1956 landslide disaster that occurred in the Lembang Fault area. A series of local wisdom emerged as important messages tucked into the procession that are related to the ritual communication concept. Based on the three interrelated terms of ritual communication: communication, communion, and commonality (Couldry,2003), this research seeks to reveal the meaning of the Hajat Lembur tradition as disaster risk reduction literacy. This research uses a case study approach, conducted by participatory observation in the Hajat Lembur ritual procession in 2023; in-depth interviews with two informants, in the form of opinion leaders who play a central role in the ritual procession; and literature reviews. The results showed that in terms of communication, the Hajat Lembur tradition is interpreted as a transcendent medium about the importance of maintaining harmonisation between humans, nature, and the Creator. In terms of communion, it is a celebration of the sacred Batu Wahyu that led to an agreement to establish a sacred forest, as an area that must be preserved. In terms of commonality, this ritual is a joint expression of the Batu Lonceng Village community about the importance of protecting nature and the environment inherited by the ancestors. Although there is a need for more established local knowledge in this area, this research contributes to the future of disaster mitigation management by emphasising rationality and local wisdom in dealing with natural disasters.